If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 + -2x + -2 = 0 Reorder the terms: 4 + -2 + 3x + -2x = 0 Combine like terms: 4 + -2 = 2 2 + 3x + -2x = 0 Combine like terms: 3x + -2x = 1x 2 + 1x = 0 Solving 2 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = 0 + -2 1x = 0 + -2 Combine like terms: 0 + -2 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 3x/4=18 | | (x)+6=157 | | 3.142x^2-x-26(3.142)=0 | | (x-4)=72 | | (4*x)/((x-1)*((x^2)+1)) | | 5+10(x-4)=848 | | 4x+6w=1/8 | | x^3-x^2+x+1= | | 9.8x-174=3.7x+628 | | -4x-22=-90 | | 10x+16=8x-1782 | | 3x^2-18x+25=0 | | 16x^2+16x-3=0 | | -3(x+6)=5+3x-7 | | 3x+3x+12-x= | | -10/25= | | 6x-(6+4x)=20 | | 5x+2+12/3x+6 | | 2(4x-4)+3=-21 | | x(4x+5)=6 | | 3d*2+23d+14=0 | | 13200-250x=5 | | -3/8/(-3/8) | | a^6-a^2=a^4-1 | | 0.25x^2-6x+36=0 | | 50x+10/60=20/30 | | x/3+x/9=8 | | 65x^2-8x-48=0 | | 4(x+1.3)=3x+7.1 | | x^2-22x+2=0 | | x^2-14x+31=0 | | 3x-3+2(2x)+17=-3-3x+(16-7) |